Effect of Copper Addition on the Phase Composition and Microstructure Evolution of Fe-Based Amorphous Alloy Coatings Prepared by Laser Cladding - Xiao Mingying; Xiu Qiang; Jiang Fengchun (Advances in Materials Science and Engineering)
Laser clad coating’s susceptibility to cracking is extremely high due to the brittleness of the material itself and the enormous residual stress caused by rapid heating and cooling. In order to relieve the residual stress, a series of Fe-based amorphous-Cu composite coatings were fabricated on 20 steel using laser processing. The effects of copper addition on the phase composition and microstructure evolution of the coatings were then investigated. The as-prepared coatings, which are mainly composed of Fe-based amorphous, Cu, and (Fe, Cr)23 (C, B)6 have a network microstructure. A large amount of spherical-shaped copper metal is present in the coating and is evenly dispersed within the amorphous matrix. The copper in the coating has little effect on the crystallisation of Fe-based amorphous alloys due to the negligible solubility of solid copper and the Fe-based amorphous alloy. The coating average hardness reduces considerably and shows a significant difference, improving the coating stress distribution.